THE EFFECTIVENESS OF COUNSELING THROUGH AUDIO VISUAL MEDIA USING ANIMATION VIDEO ON COMPLIANCE OF IRON TABLETS (FE) CONSUMPTION IN PREGNANT WOMEN AT WORKING AREA OF TANJUNG MORAWA COMMUNITY HEALTH CENTER IN 2020 - khairiatu saadah; Efendi Sianturi (Poltekkes Kemenkes Medan, 2020)
The results of Basic Health Research (Riskesdas) issued by the Health Research and Development Agency (Baritbankes) of the Indonesian Ministry of Health in 2018 stated that the prevalence of anemia in pregnant women in Indonesia was 48.9%. In North Sumatra, blood tests were carried out on pregnant women from 9,377 pregnant women in three cities, namely Medan, Pematang Siantar and Kisaran. 33% of them had anemia. One of the causes of anemia in pregnancy is iron deficiency. The type of research used was pre-experiment with One Group Pretest-Posttest Design. In this study, using purposive sampling technique, namely 34 pregnant women. Adherence is the level of patients carrying out the treatment and behavior suggested by their doctor or by others. Meanwhile, the compliance with taking blood-supplemented tablets is a behavior where pregnant women support the iron supplementation program carried out by the government to prevent anemia in pregnant women. Based on the results of the research discussion entitled